Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Berbagai Perbandingan Media Tanam Sludge dan tandan Kosong Kelapa Sawit (TKKS) Di PreeNursery pree Nur sersey - Haikal Hanif Nasution; Chairani Hanum; Ratna Rosanty Lahay (Jurnal Agroekoteknologi, 2014)
Growth of Oil Palm Seedlings (Elaeis guineensis Jacq.) with Different Comparison Sludge andEmpty Palm Oil Fruit Bunches (EPOFB) Media in Pre Nursery. Guided by CHAIRANI HANUMand RATNA ROSANTI LAHAY. The objective of this research was to study growth of oil palmseedlings at various growing media comparisons of sludge and EPOEFB in pre nursery. Thisresearch was conducted at Kebun Bangun PTPN III from January-June 2013 using non factorialrandomized block design consisted of 11 types of growing media: top soil, sludge, TKKS andcomposite media 10:80:10, 10:70:20, 10:60:30, 10:50:40, 10:40:50, 10:30:60, 10:20:70, 10:10:80.Parameters observed were shoot and root dry weight. The results showed that each media haddifferent growth characteristics. The growth media was significantly efffect on all parametersexcept plant height. Sludge can be used as a growing media if it is in the form of a mixture. If thesludge is used alone then plant growth restricted. Media composition 10:20:70 gave the best resultsthrough the highest value shoot dry weight.Keywords : growth , seeds , palm oil , sludge , TKKS